Supporting pupils exhibiting emotionally based school refusal to attend school more regularly: an interpretative phenomenological analysis exploring the experiences of secondary school staff - Pritchard, Phyllida (2019)
The majority of research exploring emotionally based school refusal (EBSR) has focussed primarily on risk factors for this behaviour and the negative trajectory for these pupils (Flakierska-praquin, Lindstrsm, & Gillberg, 1997; Van Eck, Johnson, Bettencourt, & Lindstrom-Johnson, 2017). An emerging base of literature has begun to explore school-based strategies to support pupils exhibiting EBSR to attend school more regularly, however, this base of research is currently limited and there is a lack of research focussing on ‘success stories’ of pupils exhibiting EBSR feeling able to attend school more regularly.